Design och konstruktion av stativ/golvhögtalar-hybrid - Andersson, Olov; Edman, Tanya (2013)
This paper is the result of a 30 HP Master Thesis in Technical Design, Product Design at Luleå University of Technology. This thesis is co-written by two students for a hifi company in, Torup, Halland called XTZ AB. The assignment was to design a new speaker that is a standmount speaker with additional speakers in the stand. It can therefore be seen as a hybrid between a standmount speaker and a floorstanding speaker. This hybrid was required to be powerful but to look sleek and neat. The top was also required to work as a separate speaker without the stand. To make this design more innovative additional requirements, such as the ability to face the stand either forwards or backwards, were added to set the speaker apart from its competitors. This led to a certain restriction in regards to shape but at the same time it opened up more opportunities for innovative solutions. This is an example of one of several considerations that had to be made during the design process. With these parameters in mind product development began, following the steps of the product design process. This process began with a divergent creative phase followed by a convergent phase. This was repeated until ten designs were left and these were subjected to an opinion poll to involve the end user in the development process. This poll along with the opinion of the university advisor and the company resulted in the choice of two concepts for further developments. One concept follows todays design norms to a high degree and one is more innovative in its design. The two concepts were optimized to meet the specification of requirements, both acoustically and in regards to construction and design. This phase was iterative as design affected acoustics and vice versa. This resulted in CAD files and drawings for each concept as well as simulated frequency responses for each speaker and stand. The final speakers, named Divine Hybrid and JET, both have turnable standmount. Divine Hybrid is meant to fit in XTZ’s more exclusive series Divine while JET ...